JADES Initial Data Release for the Hubble Ultra Deep Field: Revealing the Faint Infrared Sky with Deep JWST NIRCam Imaging - Marcia J. Rieke; Brant Robertson; Sandro Tacchella; Kevin Hainline; Benjamin D. Johnson; Ryan Hausen; Zhiyuan Ji; Christopher N. A. Willmer; Daniel J. Eisenstein; Dávid Puskás; Stacey Alberts; Santiago Arribas; et al. (The Astrophysical Journal Supplement Series, 2023)
JWST has revolutionized the field of extragalactic astronomy with its sensitive and high-resolution infrared view of the distant Universe. Adding to the new legacy of JWST observations, we present the first NIRCam imaging data release from the JWST Advanced Deep Extragalactic Survey (JADES), providing nine filters of infrared imaging of ∼25 arcmin ^2 covering the Hubble Ultra Deep Field and portions of Great Observatories Origins Deep Survey South. Utilizing 87 on-sky dual-filter hours of exposure time, these images reveal the deepest ever near-infrared view of this iconic field. We supply carefully constructed nine-band mosaics of the JADES bands, as well as matching reductions of five additional bands from the JWST Extragalactic Medium-band Survey. Combining with existing Hubble Space Telescope imaging, we provide 23-band space-based photometric catalogs and photometric redshifts for ≈47,500 sources. To promote broad engagement with JADES, we have created an interactive FitsMap website to provide an interface for professional researchers and the public to experience these JWST data sets. Combined with the first JADES NIRSpec data release, these public JADES imaging and spectroscopic data sets provide a new foundation for discoveries of the infrared Universe by the worldwide scientific community.